An exploratory trial of parental advice for increasing vegetable acceptance in infancy - Fildes, A (2015)
Research suggests that repeatedly offering infants a variety of vegetables during weaning increases vegetable intake and liking. The effect may extend to novel foods. The present study aimed to investigate the impact of advising parents to introduce a variety of single vegetables as first foods on infants' subsequent acceptance of a novel vegetable. Mothers of 4-to 6-month-old infants in the UK, Greece and Portugal were randomised to either an intervention group (n 75), who received guidance on introducing five vegetables (one per d) as first foods repeated over 15 d, or a control group (n 71) who received country-specific 'usual care'. Infant's consumption (g) and liking (maternal and researcher rated) of an unfamiliar vegetable were assessed 1 month post-intervention. Primary analyses were conducted for the full sample with secondary analyses conducted separately by country. No significant effect of the intervention was found for vegetable intake in the three countries combined. However, sub-group analyses showed that UK intervention infants consumed significantly more novel vegetable than control infants (32.8 (SD 23.6) v. 16.5 (SD 12.1) g; P = 0.003). UK mothers and researchers rated infants' vegetable liking higher in the intervention than in control condition. In Portugal and Greece, there was no significant intervention effect on infants' vegetable intake or liking. The differing outcome between countries possibly reflects cultural variations in existing weaning practices. However, the UK results suggest in countries where vegetables are not common first foods, advice on introducing a variety of vegetables early in weaning may be beneficial for increasing vegetable acceptance.